Pengembangan aplikasi E-UKBM kimia sebagai media pembelajaran interaktif siswa kelas XI SMAN Bali Mandara - I Wayan Madiya (Indonesian Journal of Educational Development, 2020)
This research is motivated by a lot of students who miss the subject matter, e-UKBM learning has not run effectively, the demands of e-UKBM assignments are many and HOTS, the completion time is long, and students prefer to play with friends, laptops/smartphones. The purpose of this study is to analyze (1) the chemical e-UKBM application functionality, (2) application eligibility, (3) application performance at different resolutions; and (4) the effectiveness of applications as interactive learning media. This research is an R&D research model of ADDIE which was conducted at the SMAN Bali Mandara from January-October 2019 with 27 subjects of class XI MIPA1 as the trial subjects. Product feasibility test is validated by material and media experts, alpha test, and beta test. Data collected using observation, interviews, questionnaires, and post-test were analyzed usingdescriptive analysis. The results show that (1) the chemical e-UKBM application functionality test includes ease of navigation, application performance, and operational functioning very well; (2) the feasibility of the application is based on the assessment: material experts, media experts, teachers, and students respectively are 89%, 89%, 92%, and 95% with the category "Very Eligible"; (3) application performance using smartphones with different screen sizes and RAM functions welland there are no errors; (4) the post test results show that this application has a high effectiveness, with the mean values of the experimental and control groups being 84.63 and 72.78, respectively. Penelitian ini dilatarbelakangi oleh banyak siswa ketinggalan materi pelajaran, pembelajaran e-UKBM belum berjalan efektif, tuntutan tugas e-UKBM banyak dan HOTS, waktu penyelesaian lama, serta siswa lebih suka bermain dengan teman, laptop/smartphonenya. Tujuan dari penelitian ini adalah untuk menganalisis (1) fungsionalitas aplikasi e-UKBM kimia, (2) kelayakan aplikasi, (3) unjuk kerja aplikasi pada resolusi berbeda; dan (4) keefektifan aplikasi sebagai media pembelajaran interaktif. Penelitian ini termasuk penelitian R&D model ADDIE yang dilaksanakan di SMAN Bali Mandara dari bulan Januari-Oktober 2019 dengansubjek uji coba adalah 27 orang siswa kelas XI MIPA1. Uji kelayakan produk dilakukan validasi oleh ahli materi dan media, uji alpha, dan uji beta. Data dikumpulkan menggunakan observasi, wawancara, angket, dan post test dianalisis menggunakan analisis deskriptif. Hasil penelitian menunjukkan bahwa (1) uji fungsionalitas aplikasi e-UKBM kimia meliputi kemudahan navigasi, performa aplikasi, dan operasional berfungsi sangat baik; (2) kelayakan aplikasi didasarkan pada penilaian: ahli materi, ahli media, guru, dan siswa berturut-turut adalah 89%, 89%, 92%, dan 95% dengan kategori “Sangat Layak”; (3) unjuk kerja aplikasimenggunakan smartphone dengan ukuran layar dan RAM berbeda-beda berfungsi baik dan tidak terdapat error; (4) hasil post test menunjukkan aplikasi ini memiliki efektivitas tinggi, dengan nilai rerata kelompok eksperimen dan kontrol berturut-turut 84,63 dan 72,78.